Adolescence, Sense of Identity, and Female Risk Taking in a Senior Secondary School in Northern Tasmania - Wood, Derris (EDUCARE, 2010)
ABSTRACT: This research examined risk taking with the main focus being negative risk taking and the main target adolescent females in a Senior Secondary School setting in Tasmania, Australia, using three varied methodologies and perspectives for the data collection. The first, and major method, used a questionnaire distributed to a year 11 group of females, aged sixteen to nineteen, who were just beginning their first year of non-compulsory, post secondary education. This questionnaire had the main focus of discovering their risk taking perceptions and participation rates regarding four main areas of negative risk taking, namely alcohol, and drug use and abuse, sexual activity, and the viewing of X-Rated (pornographic) videos. The socio-demographic information concentrated on the femalesâ sense of self, their personal goals, and positive and negative risk taking activities within the context of social capital, psychological, social, educational, risk taking, and health background theory and in the three domains of family, school, and community. To provide a wider perspective on the topic of risk taking, interviews were also conducted with those professionals and carers of adolescent children, namely School Administrators, Teachers, and Parents to provide information from the reality of adolescentsâ lives. The third source of data involved a review of the Australian and State Policies impinging on aspects of the curricula suitable for these adolescents. The major findings from the questionnaire emphasised that the femalesâ sense of self, parental influence and, to a lesser extent, religious values will decrease negative risk taking. KEY WORDS: Negative risk taking, adolescent females, Senior Secondary School, parental influence, and religious values.About the Author: Derris Wood, Ph.D. is a Lecturer at the School of Education UTAS (University of Tasmania), Australia. She can be reached at: dwood@iinet.net.auHow to cite this article? Wood, Derris. (2010). âAdolescence, Sense of Identity, and Female Risk Taking in a Senior Secondary School in Northern Tasmaniaâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.45-54. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 1, 2010); Revised (July 5, 2010); and Published (August 17, 2010).